From "God's Wrath" to "Miracle Birds": The Evolution of the American Drone Program and Public Opinion in FATA - Ansari, Neha. (Tufts University. Tisch Library., 2022)
Thesis (Ph.D.)--Tufts University, 2022.; Submitted to the Dept. of Diplomacy, History, and Politics.; Advisors: Ayesha Jalal, and Richard Shultz.; Committee: Stephen Wright.; Keyword: International relations.